(untitled) (Advancements in Homeopathic Research, 2025)
In their previous series of six publications, Gupta et. al. demonstrated that patients of chronic kidney disease (CKD) and acute renal failure (ARF) can be successfully managed by homoeopathic medicines. This seventh case series is on successful management of CKD patients by maintaining their serum creatinine level and eGFR within a reasonable range, delaying further deterioration and improving their quality of life for a considerable period of time without haemodialysis. The first case in this series is of 68-year old hypertensive male suffering from chronic renal failure with follow up of about 4 years. His S. Creatinine, Urea level reduced gradually and became normal with homoeopathic treatment without dialysis. His eGFR also increased and he became clinically asymptomatic. The second case is of a 42- year old hypertensive, nondiabetic female. Her S. creatinine and eGFR was maintained for more than 3 years. The third patient is a 55-year old hypertensive, nondiabetic, anaemic female. Her S. Creatinine and S. Urea gradually reduced and eGFR improved with homoeopathic treatment without dialysis. Her treatment is still continued.